Synthesis of novel acylated and esterified ciprofloxacin derivatives as efficient anticancer and antimicrobial agents - Alasadi, Gheith M.; Al-Obaidi, Zaid (Frontiers in Materials, 2023)
Nowadays, various factors enhance the resistance of some microbes to antibiotics. Irrational antibiotic use is considered an example of such factors. Therefore, the synthesis and reporting of heterocyclic compounds with multiple biological properties are of considerable value. Ciprofloxacin is an antibiotic used to treat infections. New amidification and esterification derivatives of ciprofloxacin were synthesized. Their structure was identified and confirmed using both proton and carbon-13 nuclear magnetic resonance, mass spectrometry, and elemental analysis. With the employment of the MTT (3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyl-terazoliumbromide) methods, in vitro anticancer activity was evaluated. Whereas, the utilization of clinical and laboratory standards institute (clsi) instructions, was involved in the in vitro antimicrobial activity evaluation of the newly synthesized derivatives. In anticancer activity, cell proliferation and viability and IC50, and antimicrobial activities, IZD (Inhibition Zone Diameter), MIC (Minimum Inhibitory Concentrations), MBC (Minimum Bactericidal Concentrations), and MFC (Minimum Fungicidal Concentration) were measured and reported. The lowest cell proliferation and viability and IC50 for 2,3-dihydroxypropyl 1-cyclopropyl-6-fluoro-4oxo-7-(piperazin-1-yl)-1,4-dihydroquinoline-3-carboxylate (compound 5) was observed as 27.12% and 7.83 μg/mL. In antimicrobial activity, the lowest MIC for 2,3-dihydroxypropyl 7-(4benzoylpiperazin-1-yl)-1-cyclopropyl-6-fluoro-4-oxo-1,4-dihydroquinoline-3-carboxylate (compound 6c) was observed 2 μg/mL (against Proteus mirabilis), and the lowest MIC for 1cyclopropyl-6-fluoro-7-(4-(4-(methylthio)benzoyl)piperazin-1-yl)-4-oxo-1,4-dihydroquinoline-3carboxylic acid (compound 3d) was observed 32 μg/mL (against Candida albicans, Aspergillus fumigatus). The effects were compared with commercially available drugs, and it was observed that some derivatives have the same efficacy as abemaciclib, that is used to treat breast cancer. Some derivatives were more effective than Cefazolin and Tolnaftate, well-known antibiotic and antifungal, respectively. Finally, a fairly clear relationship between the structure of the derivatives and their biological effectiveness was observed.